Musykilat Ta’lim Maharah al-Istima’ fi as-Shaff al-Hadi ‘Asyar fi al-‎Madrasah al-Aliyah al-Hukumiyah Madinah Solok - Brenda Permata (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2023)
The listening skill is one of the four language skills that students must ‎master in Arabic language education in order to obtain comprehensive ‎language skills. In Madrasah Aliyah Negeri Solok city, the teacher didn’t ‎care about the listening skill so that it would have an impact on the ‎students learning results, because they still face problems in ‎understanding the vocabulary and the students different backgroumd, ‎and the students low interest in learning. This attracts the researcher ‎to investigate the number of problems that occur in the eleventh grade ‎students in the Madrasah Aliyah Negeri Solok city. The aims of this ‎research is to explore the problems of teaching listening skill in the ‎eleventh grade, the factor influencing these problems, and solutins to ‎the problems of the eleventh grade students at the Madrasah Aliyah ‎Negeri Solok city. The research method used is descriptive qualitative ‎approach. As for the object as well as the source of research data are ‎arabic teacher and eleventh grade students. Data collection was done ‎through observation, interviews and documentation. The result of the ‎study revealed that the problems faced by students in participating in ‎listening learning activities included linguistic problems are mostly ‎caused by a lack of vocabulary, and non-linguistic problems are caused ‎by low motivation and interest